Authentication techniques in smart grid: a systematic review - Malik Qasaimeh; Rawan Turab; Raad S. Al-Qassas (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Smart Grid (SG) provides enhancement to existing grids with two-way communication between the utility, sensors, and consumers, by deploying smart sensors to monitor and manage power consumption. However due to the vulnerability of SG, secure component authenticity necessitates robust authentication approaches relative to limited resource availability (i.e. in terms of memory and computational power). SG communication entails optimum efficiency of authentication approaches to avoid any extraneous burden. This systematic review analyses 27 papers on SG authentication techniques and their effectiveness in mitigating certain attacks. This provides a basis for the design and use of optimized SG authentication approaches.